Designing plasmonic metasurface absorbers with desirable absorption values for different thermal applications. (1st May 2022) - Nagaty, Ahmed; Aly, Arafa H; Sabra, Walied
Abstract: In this paper, we demonstrate and explore an approach to designing absorbers based on using plasmonic metasurfaces in the visible spectrum. The approach opens up the possibility of rapidly choosing an absorber with the desired absorption value using an analytical expression. By using the three dimensional finite element method, we present a wide comparison between varieties of plasmonic absorbers based on using different nanoantennas in the proposed metasurface designs. The utilized plasmonic nanoantennas are such as the titanium nitride (TiN), Aluminum (Al), Gold (Au), and Silver (Ag) nanoantennas. The comparison between using these plasmonic nanoantennas will be according to the resulted absorption from the proposed designs. The plasmonic metasurfaces using the TiN nanoantennas demonstrates a high absorption compared to the obtained absorption from the other metasurface designs using (Al), (Au), and (Ag) nanoantennas. Accordingly, based on these results, we used a regression analysis to fit our simulated data to an analytical expression in order to generalize the concept of generation the absorbers of interest with the desired absorption based on the proposed metasurfaces. This promising technique provides a methodology to design preoptimized absorbers for practical applications such as sensing, thermal management, and solar cells.